2015
DOI: 10.1007/s00441-015-2190-z
|View full text |Cite
|
Sign up to set email alerts
|

Union is strength: matrix elasticity and microenvironmental factors codetermine stem cell differentiation fate

Abstract: Stem cells are an attractive cellular source for regenerative medicine and tissue engineering applications due to their multipotency. Although the elasticity of the extracellular matrix (ECM) has been shown to have crucial impacts in directing stem cell differentiation, it is not the only contributing factor. Many researchers have recently attempted to design microenvironments that mimic the stem cell niche with combinations of ECM elasticity and other cues, such as ECM physical properties, soluble biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Thus, the gelation time result indicated that the SA 2 ColI 1 may reduce the MSCs loss and provide better protection compared with SA 4 ColI 1 and SA. The rheological behavior of the hydrogels was investigated via detecting their modulus of elasticity, and the modulus values of all the hydrogels ranged from 200 Pa to 1000 Pa (Figure 3b), which were similar to the human body's tissue modulus values, and this will contribute to the interaction of the implants and the focal tissue and improve the recovery of the damaged organs (14). Wherein, the SA 2 ColI 1 presented a stable modulus values curve compared to SA 4 ColI 1 and SA, which obviously made better matching degree for the tissues and may be more beneficial to the tissue repair and regeneration.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, the gelation time result indicated that the SA 2 ColI 1 may reduce the MSCs loss and provide better protection compared with SA 4 ColI 1 and SA. The rheological behavior of the hydrogels was investigated via detecting their modulus of elasticity, and the modulus values of all the hydrogels ranged from 200 Pa to 1000 Pa (Figure 3b), which were similar to the human body's tissue modulus values, and this will contribute to the interaction of the implants and the focal tissue and improve the recovery of the damaged organs (14). Wherein, the SA 2 ColI 1 presented a stable modulus values curve compared to SA 4 ColI 1 and SA, which obviously made better matching degree for the tissues and may be more beneficial to the tissue repair and regeneration.…”
Section: Resultsmentioning
confidence: 85%
“…Different stiffness hydrogels can affect the behavior of stem cells, MSCs, fibroblasts ( Ibañez et al, 2021 ), macrophages, and other cells, thereby affecting the process of tissue repair or bone defect. In particular, hydrogels affect the phenotype of macrophages through changes in stiffness ( Lv et al, 2015 ), leading to changes in tissue inflammatory environment and angiogenesis, and ultimately promoting wound healing. How hydrogels affect the expression of related proteins or oxidative stress, leading to changes in cell behavior has become a research hotspot in recent years.…”
Section: Effects Of Hydrogel Stiffness On Tissue Repairmentioning
confidence: 99%
“…BMMSCs are of great interest for biomedical research, drug discovery, and cell-based therapies as they are capable of differentiating into neurogenic, adipogenic, myogenic, and osteogenic lineages 1 - 3 . The fate of the stem cells is influenced by the microenvironment in which they reside 4 . Although extensive efforts are devoted to identifying biochemical factors that mimic the stem cell microenvironment to maintain the stem status and to promote the differentiation if necessary, it is still a challenge to optimize new biomolecules supporting stem cell differentiation and/or producing a high level of desired lineages from the stem cells.…”
Section: Introductionmentioning
confidence: 99%